Late presentation of haemorrhagic disease of the newborn. Issue 5 (May 1984) - Alpan, G; Avital, A; Peleg, O; Dgani, Y
Abstract : A 9 week old infant presented with bleeding due to vitamin K deficiency. He had not been given vitamin K after birth but there was no associated risk factor for deficiency and he had not bled from circumcision performed at 8 days of age.